Pengaruh Penggunaan Sensor Tingkat Minyak pada Sistem Monitoring Tangki Bahan Bakar Alat Berat Bulldozer - Hasan Abdillah; Asrori Asrori (Pusat Riset dan Inovasi Nasional, 2024)
A bulldozer is a heavy equipment used to dig, push and move soil or coal material. The problem that often occurs with the D85ESS-2 bulldozer unit is that the unit often runs out of fuel. The D85ESS-2 bulldozer with serial number or SN.J11888 does not have a fuel indicator on the dashboard, so it must be checked every time. The purpose of this research is to analyze and measure the impact of the sensor rod angle and the physical condition of the float on the sensor on the accuracy of the fuel sensor. This research uses a quantitative method by modifying the size of the angle on the sensor by 75º, 85º (standard) and 95º and by adding variations in the physical condition of the float (good condition and 1 cm crack). The test was carried out using a variation in the amount of fuel of 50% or 205 liters. The results of this research indicate that the accuracy of measurements on the sensor is influenced by the physical condition of the buoy and the size of the angle. The highest result occurred at an 85º angle with a good float of 97.78%, while the lowest result was 73.32% at a 95º angle with a 1 cm cracked float condition.